Variability of nutrient absorption in several cocoa planting materials - A. Adi Prawoto; Soetanto Abdoellah (Indonesian Coffee and Cocoa Research Institute, 1990)
A study on nutrient absorption of Trinitario and Forastero cocoa types had been conducted in Kaliwining Experimental Garden and the laboratory of plant analysis of the Jember Research Institute for Estate Crops (JRIEC) since June 1987 until March 1988. Trinitario type was represented by four groups of cultivars i.e.Djati Roenggo (three DR series) Djati Roenggo Clone (13 DRC series), Kaliwining Clone (six KWC series), and Imperial College Selection (three ICS series). Forastero type was represented by two groups of cultivar, i.e. Getas Clone ( seven GC series),and Scavina (three Sea series). The seedlings of propelegitimate seeds were used. The results showed that under the same environmental condition there were significant differences between the two cocoa types in the absorption of K, Mg, Cu, and Mn. Trinitario type showed high absorption for K and Mn, but lower in the absorption of Mg and Cu compared to Forastero type. Among cultivar's group within Trinitario type there were differences in the absorption of N, P, K, Mg, Cu, and Mn. ICS group showed high absorptionfor N, KWC for P and K, DRC for Cu, ICS for Mn, and DR, DRC and ICS for Mg. In the Forastero type, GC group showed high absorption for P, but Sea group had the highest absorption capacity for K, Mg, and Mn. No significant difference was observed between the series within each cultivar group.